2009
DOI: 10.1016/j.juro.2008.10.018
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Impact of a Robot Assisted Laparoscopic Prostatectomy Mini Fellowship Training Program on Postgraduate Urological Practice Patterns

Abstract: An intensive, dedicated 5-day educational course focused on learning robot assisted laparoscopic prostatectomy enabled most participants to successfully incorporate and maintain this procedure in clinical practice in the short term and long term.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 18 publications
2
26
0
Order By: Relevance
“…Because of the significantly higher rates of patients with high-risk disease in their RRP cohort, their margin analysis was limited to low-and intermediate-risk patients. They found a positive surgical margin rate of 14% after RRP and 13% after RALP [13]. In the present study, we observed overall positive surgical margin rates of 14.4%, 13.0% and 19.5% for RRP, LRP and RALP, respectively.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Because of the significantly higher rates of patients with high-risk disease in their RRP cohort, their margin analysis was limited to low-and intermediate-risk patients. They found a positive surgical margin rate of 14% after RRP and 13% after RALP [13]. In the present study, we observed overall positive surgical margin rates of 14.4%, 13.0% and 19.5% for RRP, LRP and RALP, respectively.…”
Section: Discussionsupporting
confidence: 66%
“…LRP is a challenging technique because of its lengthy learning curve, ergonomics associated with instrumentation, and the requirement for expertise in laparoscopic surgery [10]. RARP is more attractive to many surgeons compared to LRP as a result of the more rapid transfer of open-surgery skills to a minimallyinvasive setting, three-dimensional vision, six degrees of freedom, downscaling of movements and elimination of physiological tremor [11][12][13].…”
Section: Discussionmentioning
confidence: 99%
“…At the University of California Irvine, the shortand long-term benefits of procedure-specific 5-day robotic surgery training courses have been reported. 14,15 More recently, educators at the University of Texas Southwestern have published feasibility, validity, and reliability data on a competency-based inanimate training program for robotic surgery, which also addresses the need for structured training programs. 16 Surgical training literature has clearly demonstrated the superior educational outcomes associated with curricula that adhere to the principles of spaced-learning and competency-based training.…”
Section: Discussionmentioning
confidence: 99%
“…Already in 2001, Chitwood et al [24] proposed a similar curriculum, wildly used by others centers with success. Mini-fellowships of 1 week or more were reported as well [16,17]. After a mini-residency program of 5 days, McDougall et al [17] reported 95 % of participants practicing robotic prostatectomy, and even to maintain this procedure in clinical practice in the long-term [16].…”
Section: Discussionmentioning
confidence: 99%